2000
DOI: 10.1034/j.1600-0706.2000.900314.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratification based on reproductive state reveals contrasting patterns of age‐related variation in demographic parameters in the kittiwake

Abstract: Heterogeneity in individual quality can be a major obstacle when interpreting age‐specific variation in life‐history traits. Heterogeneity is likely to lead to within‐generation selection, and patterns observed at the population level may result from the combination of hidden patterns specific to subpopulations. Population‐level patterns are not relevant to hypotheses concerning the evolution of age‐specific reproductive strategies if they differ from patterns at the individual level. We addressed the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 46 publications
4
68
1
1
Order By: Relevance
“…We see several explanations for this apparently contradictory result. An age effect can be masked by individual heterogeneity [11], which was not accounted for here, or may be detectable only when accounting for other covariates [23]. Alternatively, while many experienced individuals are reobserved at oldest ages, none of the inexperienced individuals reached old ages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We see several explanations for this apparently contradictory result. An age effect can be masked by individual heterogeneity [11], which was not accounted for here, or may be detectable only when accounting for other covariates [23]. Alternatively, while many experienced individuals are reobserved at oldest ages, none of the inexperienced individuals reached old ages.…”
Section: Discussionmentioning
confidence: 99%
“…Again, experience was not taken into account, and the analysis required selection of a specific subset of individuals confined in a given spatial unit. In addition, it was previously suggested that the approach used to define clusters of individuals breeding in the same spatial units (cliffs) was not satisfactory [23]. Indeed, the number of pairs in such units ranged from 10 to 300; unless there was no heterogeneity in breeding activity and success in the unit (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations